Comparison of intubating conditions during rapid sequence induction between rocuronium with magnesium sulphate pretreatment and succinylcholine in patients undergoing elective surgery under general anaesthesia - prospective randomized study. - Nivedha Rajasekaran; Nisha Kachru; Nidhi Yadav; Rupesh Yadav (Critical Care Innovations)
INTRODUCTION: Rapid sequence induction is a conventional method used for airway management during anesthesia. Succinylcholine is considered standard neuromuscular blocking agent in rapid sequence induction but avoid the side effects of succinylcholine, rocuronium used as an alternative. Magnesium given as pretreatment before standard dose of rocuronium shortens the duration of onset of action of rocuronium and improve the intubating conditions. Aim of the study was to compare intubating conditions during rapid sequence induction between rocuronium with magnesium sulphate pretreatment, and succinylcholine in patients undergoing elective surgery under general anaesthesia. MATERIALS AND METHODS: In this Prospective comparative study, 150 patients were divided into 2 groups of 75 each. Group 1 patients were pretreated with magnesium sulphate 50 mg/kg in 100 ml 0.9% normal saline before induction and administration of rocuronium 0.6 mg/kg for intubation. Group 2 patients were given 100ml 0.9% normal saline before induction and succinylcholine 1.5 mg/kg was given for intubation. Intubating conditions were graded as excellent (score 8- 9), good (score 6-7), fair (3-5), poor (0-2) according to Cooper’s criteria. RESULTS: In 74 patients in each group, jaw relaxation was easy and in 1 patient in each group, it was fair (p=1). Vocal cords were found to be abducted in 70 patients (93.3%) in group 1 and 74 patients (98.7%) in group 2. Vocal cords were moving in 5 patients (6.6%) and 1 patient (1.3%) in group 1 and 2 respectively (p=0.209). There was no response to intubation in 67 patients (89.3%) and 73 patients (97.3%) in group 1 and 2 respectively. 8 patients (10.6%) in group 1 and 2 patients (2.7%) in group 2 had slight diaphragmatic movement. (p=0.097). 71 patients (94.6%) in group 1 and 74 patients (98.7%) in group 2 had excellent intubating conditions. 4 patients in group 1 and 1 patient in group 2 had good intubating conditions. Intubating conditions were comparable between both the groups (p=0.366). CONCLUSIONS: The study concluded that magnesium pretreatment before 0.6 mg/kg rocuronium provides clinically acceptable intubating conditions similar to succinylcholine making it suitable for rapid sequence induction with mild adverse effects which resolve spontaneously without any treatment.